ChemInform Abstract: Cs2AgBiX6 (X: Br, Cl): New Visible Light Absorbing, Lead‐Free Halide Perovskite Semiconductors. Issue 20 (April 2016) - McClure, Eric T.; Ball, Molly R.; Windl, Wolfgang; Woodward, Patrick M.
Abstract: The title compounds are synthesized from hot solutions containing HX (X: Cl, Br), H3 PO2, AgX, and BiX3 by precipitation with CsX, and by solid state reaction of cesium, silver, and bismuth halide salts in a 2:1:1 molar ratio (alumina crucible, 210 °C, 10 h).